Constitutional function assigned to the penalty: Bases for a criminal policy plan - Chang Kcomt, Romy Alexandra (Pontificia Universidad Católica del Perú, 2013)
This article intends to analyze treatment and functions assigned to the penalty by our Peruvian Constitution and the way this legal institution is conducted at the prescribed basic penalty level (imposed by the legislator ineach type of criminal offence), the specific penalty level (imposed by the judge according to its individual characteristics in each case) and at the penitentiary enforcement level. Finally recommends some considerations for carrying out a possible legislative reform in accordance with a criminal policy plan within our constitutional framework.